Influence of Auditory Intellectually Repetition (AIR) and Self Efficacy Learning Models on HOTS Problem-Based Problem Solving Ability - Rizal Kamsurya; Veni Saputri (Lembaga Penelitian dan Pendidikan Mandala, 2020)
This research aims to determine the differences in problem-solving skills in students taught using auditory intellectual repetition (AIR) learning models and conventionally reviewed from the self-efficacy level. The type of research used is a quasi-experimental design. The research population is high school students in the South Jakarta area. Determination of samples using random cluster sampling and stratified random sampling. The instruments used are problem-solving tests and non-test instruments that are questionnaires. Analyze data using two-lane Variance Analysis. Data analysis shows that; (1) there are significant differences in problem-solving skills in students using air learning models and conventional learning, (2) there are differences in problem-solving skills in students with high, medium, and low self-efficacy, (3) there is a significant interaction between AIR learning and self-efficacy to problem-solving ability, (4) there are significant differences in problem-solving skills between groups of students in AIR learning and conventional learning that have high self-efficacy, (5) there are significant differences in problem-solving skills between groups of students in AIR learning and conventional learning who have moderate self-efficacy, and (6) there are significant differences in problem-solving skills between groups of students in AIR learning and conventional learning who have low self-efficacy.